2014
DOI: 10.1063/1.4865836
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and numerical investigation of the dependency on the initial conditions of the Richtmyer-Meshkov instability

Abstract: International audienceThe nonlinear evolution of 2D single-mode Richtmyer-Meshkov instabilities is investigated through experiments in shock tube and numerical simulations. In our shock tube, the interface is materialized by a thin membrane attached to a stereo-lithographed grid. The purpose of this study is to compare experimental and numerical results, verify that using a higher Mach number for the incident shock wave (M-isw) than in a previous study [C. Mariani, M. Vandenboomgaerde, G. Jourdan, D. Souffland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 47 publications
4
41
0
Order By: Relevance
“…As a result, the feed-back on the first harmonics stays low: the influence of the grid on the first harmonics remains limited. These conclusions are in accordance with the ones which were drawn from a previous study [34] in the planar case: the grid adds short-wavelength (swl) perturbations to the singlemode interface with low feed-back on the fundamental mode. Another way to check that our experiment is a good approximation of the canonical single mode problem is to reconstruct the shape of the interface with the first three modes.…”
Section: Influence Of the Gridsupporting
confidence: 92%
“…As a result, the feed-back on the first harmonics stays low: the influence of the grid on the first harmonics remains limited. These conclusions are in accordance with the ones which were drawn from a previous study [34] in the planar case: the grid adds short-wavelength (swl) perturbations to the singlemode interface with low feed-back on the fundamental mode. Another way to check that our experiment is a good approximation of the canonical single mode problem is to reconstruct the shape of the interface with the first three modes.…”
Section: Influence Of the Gridsupporting
confidence: 92%
“…It is noteworthy that the spectrum of small-amplitude short-wavelength perturbations observed is inevitable in real-life experiments where the interface is machine made. In fact, it has been shown that running numerical simulations with the addition of such residual perturbations to single-mode interfaces is necessary to understand the morphology of the experimental picture (Vandenboomgaerde et al 2014). As such, the deviation in experiments herein from the ideal case of a pure single-mode perturbation allows us to complement single-mode work by improving them to be closer to reality.…”
Section: Interface Characterizationmentioning
confidence: 99%
“…Since the interface formed is not perfectly sinusoidal, the presence of a spectrum of residual small-amplitude short-wavelength perturbations (Vandenboomgaerde et al 2014) and multi-mode fronts observed can cause mode coupling (Rupert 1991) in the nonlinear late-time growth regime. Large scales develop by means of a bubble-competition mechanism (Zufiria 1988) and vortex pairing.…”
Section: Mixing Widths and Scalingmentioning
confidence: 99%
“…More precisely, the building blocks of the egg-box initialization contain two sine functions in each direction a 0 cos 2px=m ð ÞÀ 1=5 ð Þ ð cos 2px=m ð Þ Þþa 0 cos 2py=m ð ÞÀ 1=5 ð Þcos 2py=m ð Þ ð corresponding to the first harmonics of j cos px=m ð Þj or j cos py=m ð Þj. However, such a representation may not be the most realistic [22]. Furthermore, schlieren pictures ( Fig.…”
Section: Egg-box Versusmentioning
confidence: 99%